MEMBENTUK KARAKTER JIWA WIRAUSAHA MELALUI PERMAINAN ROLEPLAY DARI HASIL PEMBUATAN AKSESORIS PADA ANAK PANTI ASUHAN UNTUK MEMBANGUN KESADARAN NILAI EKONOMI - Fitrah, Muhammad Nazar; Tasmania, Tasmania; Nurhadisah, Adilla; Chandra, Silvana Aprilia (Jurnal Pajak Populis, 2025)
This community service program aims to introduce basic entrepreneurial values to children in an orphanage through a roleplay-based simulation of buying and selling activities. The program focuses on simple economic concepts, financial literacy, product value, and social interaction in trading without involving the production of goods due to time and budget limitations. The methods used include short lectures, demonstrations, and interactive simulations using toy money, cashier tools, and sample accessory products. The activities were conducted at a partner orphanage and involved children as participants who played the roles of buyers and sellers. The results showed a significant increase in the children’s understanding of basic economic concepts, decision-making skills, and awareness of product value. The program also fostered communication, cooperation, and confidence during the trading simulation. This PKM creates a meaningful learning experience that can support the development of entrepreneurial character from an early age and can be replicated in similar community settings.